البحوث المنشورة في مجلة بيت الحكمة: دراسة تحليلية - وادي، فريال حسن (جامعة عين شمس - كلية الآداب, 2018)
Published Researchers in Buyt-Al hukmih Magazine: Analytical Study By Feryal Hasan Wadi The study aims to identify publications in varions specialties issued in Buyt-Al hukmih in Arabic and English for the period (1998-2016). Moreover, the study concernes on objective and temporal analysis of these publications, and recognizing the most productive researchers and the more Authoring subjects . Furthermore, the study clarify the thematic trends of the main and sub – published topics. The study used the survey method in analyzing information of (58) magazines, the study has come up with the following results: 1- The male authors received the highest per contage in the magazine which is (78.59%) . 2- The political subjects received the highest percontuge issued which is (28.5%). On the basis of the results stated above , the following recommendation can be put forward: 1- Holding seminars and lectures to encowye females to contribut their scientific production, and publish them on special occasion such as (the woman day) and (the knowledge say), this strengthens their role in supporting the mayazine. 2- The publishing committee needs marketing to the magazine, for the purpose of contributing and publithinng it in other departments and scientific disciplines ; such as publishing the magazine electronically, and establishing a website through which researchers can contact the magazine
تهدف الدراسة إلى التعرف على واقع النتاج الفكري المنشور في مجلة بيت الحكمة في مختلف الاختصاصات الصادرة باللغة العربية والإنكليزية للفترة (1998-2013) وتحليلها موضوعياً وزمنياً ومعرفة أكثر الباحثين نتاجاً وأكثر الموضوعات تأليفاً وبيان الاتجاهات الموضوعية الرئيسة والفرعية المنشورة، واستخدمت الدراسة المنهج المسحي في تحليل بيانات المعلومات للمجلة التي تألفت من (58) عدد وخرجت الدراسة بعدة نتائج أبرزها: 1- حصل المؤلفين الذكور أعلى نسبة تأليف في المجلة وكانت (87.59 %) 2- حقق موضوع السياسة أعلى نسبة تأليف وكانت (28.5 %). وقدمت جملة من التوصيات أبرزها: 1- عقد ندوات ومحاضرات حول تشجيع الإناث في المساهمة لزيادة نتاجاتهم العلمية ونشرها من خلال استغلال واستثمار المناسبات الخاصة كعيد المرأة أو يوم الجامعة أو يوم العلم، وهذا يعزز دورها في رفد المجلة ودعمها في نشر البحوث. 2- تحتاج هيئة النشر التعريف والتسويق بالمجلة لغرض المساهمة والنشر فيها في الأقسام والتخصصات العلمية الأخرى، مثل إصدار المجلة إلكترونياً ولها موقع يمكن المشاركة والاتصال والنشر بها وغيرها في أدوات وسائل الإعلان.
Keywords: المجلات العلمية -- الانتاج الفكرى -- مجلة بيت الحكمة